Chronic wounds and novel therapeutic approaches. (1st December 2020) - Azevedo, Maria; Lisboa, Carmen; Rodrigues, Acácio
Abstract : In the past decade, the frequency of chronic wounds in older population has increased, and their impact on quality of life is substantial. Chronic wounds are a public health problem associated with very high economic and psychosocial costs. These wounds result from various pathologies and comorbidities, such arterial and venous insufficiency, diabetes mellitus and continuous skin pressure. Recently, the role of infection and biofilms in the healing of chronic wounds has been the subject of considerable research. This paper presents an overview of various methods and products used to manage chronic wounds and discusses recent advances in wound care. To decide on the best treatment for any wound, it is crucial to holistically assess the patient and the wound. Additionally, multiple strategies could be used to prevent or treat chronic wounds.